Effective and persistent changes in household energy-saving behaviors: Evidence from post-tsunami Japan. (1st April 2016) - Fujimi, Toshio; Kajitani, Yoshio; Chang, Stephanie E.
Highlights: Some households' adaptations to electricity shortage can be new efficient habits. The electricity shortage in Japan was used as a natural experiment. Some behaviors contributed to 2–4% electricity savings and persisted for two years. Behaviors requiring frequency and discomfort cannot be effective or persistent. Lowering the electricity-usage level of appliances might be a promising behavior. Abstract: This paper focuses on households' development of new energy-efficient habits as demonstrated in the context of a major electricity shortfall event. Energy conservation policies should encourage households to take measures that are actually effective in reducing energy consumption and that can be sustained over long periods of time. Few studies, however, have empirically examined what types of energy-saving measures are actually effective and persistent. The electricity shortages following the 2011 Great East Japan earthquake, tsunami, and nuclear disaster provided an opportunity to examine this question. A web survey of households in Japan was implemented to obtain data on metered electricity use in the summers of 2010–2013, household behaviors for electricity savings, and household socioeconomic attributes. Regression analysis was conducted to explain the effectiveness and persistence of energy saving behaviors. Results indicate that most households took several electricity-saving measures after the disaster to adapt to the electricity shortage. Certain types of measures led to 2–4% savings in electricity consumption (per measure) and persisted for two years. The effective and persistent electricity-saving measures tended to be those that did not require either frequent efforts or considerable discomfort. Findings suggest that electricity-saving behaviors requiring infrequent effort and little discomfort can become engrained as new habits or lifestyles. In particular, one promising measure may be to lower the electricity-usage settings of appliances.